Perkembangan Pertubuhan Seni Silat Pusaka Gayong Kedah 1956-1987 - Muhamad Azannudin Mohd Ashari (Tanjong Malim, 2023)
Perkembangan Pertubuhan Seni Silat Pusaka Gayong Kedah 1956-1987 by Muhamad Azannudin Mohd Ashari